2017
DOI: 10.1080/00346764.2017.1286032
|View full text |Cite
|
Sign up to set email alerts
|

Quality upgrading in Ethiopian dairy value chains: dovetailing upstream and downstream perspectives

Abstract: In this article, we analyze opportunities and constraints for upgrading product quality in the dairy value chain in Ethiopia. Our analysis is based on an integrated understanding of supply chain performance both from producer and from consumer perspectives. We outline as main drivers for quality upgrading: (a) factors that influence producers' willingness to invest toward intensification by smallholder dairy farmers and cooperatives and (b) factors that induce consumer's willingness to pay for healthy and nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 39 publications
1
37
1
Order By: Relevance
“…The Dairy farmers were highly complaining on the low milk production potential of their cows. It is consistent with the previous study reported by Ruerd Ruben et al [8] which says, in central part of Ethiopia the average milk output per cow remains too low for reaching economies of scale in production. As a reason poor production genotype, poor feeding and management system and reoccurrence of disease was reported during focus group discussion.…”
Section: Overview Of Cooperatives Milk Production Potentialsupporting
confidence: 83%
See 2 more Smart Citations
“…The Dairy farmers were highly complaining on the low milk production potential of their cows. It is consistent with the previous study reported by Ruerd Ruben et al [8] which says, in central part of Ethiopia the average milk output per cow remains too low for reaching economies of scale in production. As a reason poor production genotype, poor feeding and management system and reoccurrence of disease was reported during focus group discussion.…”
Section: Overview Of Cooperatives Milk Production Potentialsupporting
confidence: 83%
“…However, there is high demand for processed dairy products in tourist destiny sites like Aksum, Gonder, Lalibela, and so on. It is contrast with the reports of Ruerd Ruben [8] who stated that consumer demand for improved dairy products is also limited, thus restricting their willingness to purchase higher quality dairy products. Since, Aksum is one of the centers of tourists, different types of processed dairy products are highly demanded.…”
Section: Demand Of Processed Dairy Products In Aksum and Adwa Townscontrasting
confidence: 52%
See 1 more Smart Citation
“…Hattersley [53] used a nutrition-oriented value chain approach to study changes in the processed deciduous fruit market in Australia. Around half (i.e., 16) of the studies concerned countries in Sub-Saharan Africa, including Burkina Faso, Cote d'Ivoire, Democratic Republic of Congo, Ethiopia, Ghana, Kenya, Malawi, Mozambique, Liberia, Senegal, South Africa, and Uganda [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. The next most frequently studied region was South Asia (9 studies), including Afghanistan, Bangladesh, and India [13,56,57,[70][71][72][73][74][75].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Wesana et al [69] applied lean manufacturing principles in assessing opportunities to reduce losses in dairy value chains in Uganda. Value chains might also become more efficient through interventions which reduce transaction costs, such as public investment in road and telecommunication infrastructure [67]. Many nutritious foods are highly perishable, meaning that business transactions and the movement of produce must occur swiftly.…”
Section: Impact Pathways Related To Increasing the Accessibility Of Nmentioning
confidence: 99%